Evaluation of human resources proportion to the volume of services provided in hospitals affiliated to Kerman University of Medical Sciences - Maryam Yazdanpanah; Shirin Jafarzadeh; Nouzar nakhaee; Abbas Kamyabi; Mohammadreza Amiresmaili (Kerman University of Medical Sciences, 2018)
Evaluation of the Ratio of Human Resources to the Amount of Services Provided in Hospitals of Kerman Province   Yazdanpanah Maryam1, Jafarzadeh Shirin1*, Nakhaee Nozar2, Kamyabi Abbas1, Amiresmaili Mohammad Reza3 1. MD, Kerman University of Medical Sciences, Kerman, Iran 2. Professor, Department of Community Medicine, Kerman Neuroscience Research Center, Kerman University of Medical Sciences, Kerman, Iran 3. Associate Professor, Department of Health Management, Policy and Economic, Kerman University of Medical Sciences, Kerman, Iran Abstract: Background & Objectives: The combination and distribution of human resources is one of the major factors affecting the quality, quantity, cost, and speed of provision of health services. Today, one of the most important problems of human health systems is the inappropriate distribution of human resources. The aim of this study was to investigate the ratio of human resources to the amount of services provided in hospitals affiliated to Kerman University of Medical Sciences. Methods: This descriptive cross-sectional study was conducted during March 2015 to February 2016, to review the occupational categories of nursing staff, midwife, patient carrier, and unit secretary in 10 teaching and non-teaching hospitals in Kerman province using three methods of Workload Indicators of Staffing Need (WISN), systematic approach, and bed occupancy rate (BOR). Data were collected using a form contains job descriptions, the quantity of services provided per year by the occupational categories studied, the standard of activity time, the work time available to the hospital staff, and bed occupancy rate in the units studied.. Results: The systematic approach showed the highest need for human resources, and then, the bed occupancy ratio and WISN respectively showed the highest need, which however, depended on the hospital unit. So that, in calculating the required number of nurses in the intensive care and burn units, the index proposed by the Ministry of Health in bed occupancy rate was higher than the WISN, and the index obtained in the emergency department, was higher than the WISN. Conclusion: It is suggested to replace traditional methods with modern human resources estimation systems, as WISN. Also, it is recommended to measure the time and activities of hospital units to determine the ratio of staff to bed for each hospital.   Keywords: Teaching hospital, Non-teaching hospital, Human resources, Nursing staff   Citation: Yazdanpanah M, Jafarzadeh S, Nakhaee N, Kamyabi A, Amiresmaili MR. Evaluation of the Ratio of Human Resources to the Amount of Services Provided in Hospitals of Kerman Province. Journal of Health Based Research 2018; 4(1): 95-108. [In Persian]